Nutritional supplements and herbal medicines for women with polycystic ovary syndrome; a systematic review and meta-analysis - Susan Arentz; Caroline A. Smith; Jason Abbott; Alan Bensoussan (BMC, 2017)
Abstract Background Polycystic ovary syndrome (PCOS) is a common, reproductive endocrinopathy associated with serious short and long term health risks. Many women with PCOS use ingestible complementary medicines. This systematic review examined the effect on menstrual regulation and adverse effects from randomised controlled trials. Methods Randomised controlled trials (RCTs) that compared herbal or nutritional supplements to placebo or active controls in women with PCOS were eligible for inclusion. Electronic databases were searched to July 2017. Study selection and assessment of quality were conducted independently by two review authors. Results Twenty four studies (1406 women) investigating seven nutritional supplements and four herbal medicines were included. No one study was assessed as having a low risk of bias. Four trials reported on the primary endpoint menstrual regulation. There was no evidence on improved menstrual regularity for calcium plus vitamin D compared to Metformin (RR: 0.66, 95% CI 0.35 to 1.23, p = 0.19), reduced amenorrhoea for Camellia sinensis compared to placebo (RR: 0.17, 95% CI 0.02 to 1.72, p = 0.13) and no difference in the number of menses per month for Cinnamomum sp. against placebo (MD 0.05, 95% CI -0.36 to 1.36, p = 0.26). Adverse effects were investigated in seven studies (164 women). Mild adverse effects were found for Cinnamomum sp. compared to placebo (17 women, RR: 0.36, 95% CI 0.03 to 0.70, p = 0.03). No difference was found for adverse effects between inositol, B complex vitamins, vitamin D, chromium and placebo. Improved reproduction, metabolic hormones and hyperandrogenism was found for inositol and improved cholesterol for omega three fish oils. Conclusion There is no high quality evidence to support the effectiveness of nutritional supplements and herbal medicine for women with PCOS and evidence of safety is lacking. High quality trials of nutritional supplements and herbal medicines examining menstrual regulation and adverse effects in women with PCOS are needed.